MdMYB52 regulates lignin biosynthesis upon the suberization process in apple - Xu, Xuan; Guerriero, Gea; Berni, Roberto; Sergeant, Kjell; Guignard, Cedric; Lenouvel, Audrey; Hausman, Jean-Francois; Legay, Sylvain (Frontiers in Plant Science, 2022)
Our previous studies, comparing russeted vs. waxy apple skin, highlighted a MYeloBlastosys (Myb) transcription factor (MdMYB52-like), which displayed a correlation with genes associated to the suberization process. The present article aims to assess its role and function in the suberization process. Phylogenetic analyses and research against Arabidopsis thaliana MYBs database were first performed and the tissue specific expression of MdMYB52-like was investigated using RT-qPCR. The function of MdMYB52-like was further investigated using Agrobacterium-mediated transient overexpression in Nicotiana benthamiana leaves. An RNA-Seq analysis was performed to highlight differentially regulated genes in response MdMYB52-like. Transcriptomic data were supported by analytical chemistry and microscopy. A massive decreased expression of photosynthetic and primary metabolism pathways was observed with a concomitant increased expression of genes associated with phenylpropanoid and lignin biosynthesis, cell wall modification and senescence. Interestingly key genes involved in the synthesis of suberin phenolic components were observed. The analytical chemistry displayed a strong increase in the lignin content in the cell walls during MdMYB52 expression. More specifically, an enrichment in G-Unit lignin residues was observed, supporting transcriptomic data as well as previous work describing the suberin phenolic domain as a G-unit enriched lignin-like polymer. The time-course qPCR analysis revealed that the observed stress response, might be explain by this lignin biosynthesis and by a possible programmed senescence triggered by MdMYB52-like. The present work supports a crucial regulatory role for MdMYB52 in the biosynthesis of the suberin phenolic domain and possibly in the fate of suberized cells in russeted apple skins.